Microscopic investigations of Ocotea paranaensis―A Brazilian endemic and endangered species. Issue 10 (25th June 2022) - Gribner, Caroline; Barbosa, Vanessa; Monteiro, Luciane Mendes; Swiech, Juliane Nadal Dias; Raman, Vijayasankar; Manfron, Jane; Miguel, Obdulio Gomes; Montrucchio, Deise Prehs; de Fátima Gaspari Dias, Josiane
Abstract: This article describes the morpho‐anatomies of the leaves and stems of Ocotea paranaensis Brotto, Baitello, Cervi & Santos (Lauraceae) using light and scanning electron microscopy. The main anatomical features characterizing the species are the presence of simple non‐glandular trichomes in the leaves and stems, large secretory cells in the leaves, flat‐convex petioles with two small lateral ribs, brachysclereids in the stem cortex and pith, and the presence of starch grains and various types of calcium oxalate crystals in the pith. Histochemical tests indicated the presence of lignin in stone cells, fibers, and xylem. Lipophilic contents were found in the secretory cells. Phenolic compounds were detected in the epidermis, hypodermis, phloem, and xylem. The present study's findings can contribute to the taxonomy and authentication of O. paranaensis . Research highlights: This article is the first morpho‐anatomical study of Ocotea paranaensis . Anatomy and histochemistry of the leaves and stems were studied by light microscopy, FESEM and EDS. The findings of this study would aid in the species identification and taxonomy. Abstract : Morpho‐anatomy of leaves of Ocotea paranaensis (b, e: light microscopy, sections stained with safranin; c, d, f, g: FESEM). a: a twig of plant. b–g: leaf epidermis in surface view (b, c: adaxial side; d–g: abaxial) (ct, cuticle; md, midrib; nt, nonglandular trichome; st, stomata; wa, epicuticular wax). Scale bars: a = 2 cm, d, f = 100, b, c, e = 50, g = 20 μm.